ANALISIS KARAKTERISTIK PEMASARAN PRODUK DIMSUN DAN NILAI TAMBAHNYA PADA USAHA KECIL DAN MENENGAH DIMSUM INMONS DI KECAMATAN CIBEUNYING KIDUL KOTA BANDUNG - Junianto, Junianto; Syauqibi, Achmad; Fauzan, Muhamad; Farhansyah, Muhammad (Universitas Pattimura, 2024)
Dimsum Inmons is one of the SMEs engaged in processing fishery products in Bandung City. This study was conducted to analyze business management characteristics and measure the added value generated by Dimsum Inmons SMEs in Bandung City. The aim is to provide useful information for the development of Dimsum Inmons and similar SMEs in the future. The methods used include interviews with SME owners, direct observation to the production site, and value-added analysis using the Hayami method. The results showed that Dimsum Inmons SMEs have effective business management with dynamic market segmentation and marketing strategies through social media. The value-added analysis resulted in a value-added ratio of 78.41% which is classified as high, with a profit of Rp171,800 per kg of product. The conclusion of this study is that Dimsum Inmons SMEs have good business management characteristics and are able to generate significant added value from the processing of fishery products. Suggestions given include continuing to innovate in developing products, improving marketing strategies through social media, maintaining good business management consistency, considering market expansion, and conducting periodic evaluations of the production process and value-added analysis.